PRINSIP ITIKAD BAIK DALAM GANTI KERUGIAN OLEH PENANGGUNG KEPADA TERTANGGUNG - Gunita Nindya; Siti Nurbaiti (Fakultas Hukum Universitas Trisakti, 2022)
One kind of loss insurance is motor vehicle insurance. It frequently results in issues with its application, namely those with the application of the good faith principle, as in Criminal Code Article 251. discussions like the one that took place between the insured and PT Asuransi Astra Buana. Problem Statement: Based on the Commercial Code, how is the arrangement regarding the principle of good faith applied to the compensation given to the insured by PT Asuransi Astra Buana, and whether the insured party's actions constitute a breach of the principle of good faith? The study's methodology is descriptive in character and falls under the category of normative legal research. Secondary data is qualitatively examined by deductively drawing conclusions. The research findings, discussion, and conclusion that the arrangement of the good faith principle contained in Article 251 of the Criminal Code contains weaknesses because it is only addressed to the insured, so the insurer does not pay compensation to the insured on the grounds that the insured violates the good faith principle, and the actions taken by the insured do not violate the principle good faith, as stipulated in Article 251 of the Criminal Code.